The herpes simplex virus immediate-early protein, ICP4, is required to potentiate replication of human immunodeficiency virus in CD4+ lymphocytes. - Albrecht, M A (1989)
The interaction of human immunodeficiency virus (HIV) and herpes simplex virus (HSV) was investigated in an acute whole-virus coinfection system. CD4+ lymphoid CEM cells were infected with HIV-1 and, 24 h later, superinfected with HSV-1 (strain KOS) or HSV mutants possessing defined deletions in genes specifying the immediate-early transcriptional regulatory proteins ICP0, ICP4, or ICP27. Marked potentiation of HIV replication was demonstrated with the KOS strain, the ICP0 mutant, and the ICP27 mutant, but not with the ICP4 mutant, indicating that ICP4 is essential and ICP0 and ICP27 are nonessential for this effect. These studies demonstrate that HSV can be a potent stimulator of HIV replication and gene expression in coinfected CD4+ cells through the activity of the HSV regulatory protein ICP4.